(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2022)
Gravity measurements have been conducted, 169 gravity measurement data points with varied heights at each measuring point from 16 to 595.1 meters above sea level which is divided into two measurement paths. With the distance between the measuring points at a certain variation interval (effective 750 meters), using a closed loop method that aims to map subsurface conditions to Identifiying Structural Geology in the Bogor, West Java-Indonesia region. Complete Bouguer Anomaly (CBA) values varies from 26 mGal to 66 mGal. The High Anomalous Area, has a value of > 46 mGal, occupies more than the southern half of the study area, extends in the southwest to the possibility of symmetry in the east, and there is the highest anomaly between them. This high anomaly area is produced by a rock mass that has a greater mass density (≥ 2.507647059 gr/cm3). The Low Anomaly Area, has a value of ≤ 46 mGal, occupying less than half of the research area in the north. Increasing the anomaly value in the north on the map, forming an indication pattern of an open basin. This low anomaly area is produced by a rock mass which has a lower mass density (≤ 2.507647059 gr/cm3). Rock density at the study area based on forward modeling shows values in the range of 1.8 gr / cm3 s.d. 2.67 gr/cm3. The results of the study using gravity method based on 2D cross section shows that the main fault in bedrock along the AA ’research path is relatively West - East, with stratigraphic direction of each constituent rock layer to the south. The direction of the fault forms block faulting, making this area graben.